Interventional Effects Comparison of Intermittent Exercise Programs of Different Intensity on College Students’ Physical Health - Pei, Jiayi (International Journal of Social Sciences and Public Administration, 2025)
The physical health problems of contemporary college students need to be solved urgently, and the traditional physical education curriculum is difficult to meet the individual needs. In this paper, by comparing the high-intensity (≥ 80% HRmax) and medium-intensity (60% -75% HRmax) intermittent exercise programs, we explored the differences of their intervention effects on college students’ physical health. The results show that high-intensity interval exercise has a significant effect on improving body composition and cardiopulmonary function, especially on reducing the percentage of body fat and increasing the maximum oxygen uptake; while the moderate intensity program has more advantages in blood pressure regulation and exercise safety. The two regimens produced specific intervention effects through different physiological mechanisms. The high-intensity regimen mainly exerted its effects through metabolic stress and neuromuscular stimulation, while the medium-intensity regimen focused on fat mobilization and insulin sensitivity improvement. Based on these findings, it is suggested that hierarchical implementation strategies should be adopted according to individual differences of students, and sports intervention should be organically combined with campus physical education curriculum to provide theoretical basis and practical guidance for the formulation of scientific and personalized health promotion programs.